Option valuation with the Heston model - Ehlert, Yannik (2022)
This thesis is divided into two parts. The first part explains the theoretical background of option valuation and guides through the actual derivation of the Heston Model. The model is explained, examined and optimized. To value American options in the Heston model as well, the Finite Difference Method is applied in the Heston Model. For a comparison, the Black-Scholes-Merton Model and the Cox-Ross-Rubinstein Model are introduced. The second part deals with more practical topics: a parameter analysis, the calibration of the model using real market data and the actual calculation of European and American option prices with the Heston Model and mentioned peer models. For the application of the model and the derivation of all graphical content, the MATLAB program is used. The general focus lies in the determination of the quality of the model, which be examined by comparing the Heston values to the real market data and the peer model values. The results are critically evaluated in terms of accuracy and effort. Finally, advantages and disadvantages of the Heston Model will be discussed in extension.